PENGURANGAN GAS RUMAH KACA DARI LIMBAH CAIR DI PABRIK KELAPA SAWIT PINANG TINGGI, JAMBI DENGAN CDM - Irhan Febijanto (BPPT)
Waste water produced from Crude Palm Oil’s process in Palm Oil Mill (POM) is usually treated using water treatment ponds that consist of anaerobic ponds and aerobic ponds. It is known well, methane gas is generated from degradation of organic matter in anaerobic ponds. The methane gas results global warming impacts. Regarding to tackle the global warming impact, the methane gas generated from POM can be captured and flared to convert methane gas tocarbon dioxide. This study was conducted in one of the big capacity of Pinang Tinggi POM owned by PT Perkebunan Nusantara 3. Methane gas potential was investigated by using pH, COD (Chemical Oxygen Demand) and waste water measurement. And from these result the methane gas potential was predicted. In this study, using Clean Development Mechanism (CDM), capturing methane gas generated from anaerobic pond gave a result that the project can be an economically feasible based on the condition measured.Keywords : oil palm industry, methane gas, gas rumah kaca, CDM project(CleanDevelopment Mechanism), COD (Chemical Oxygen Demand)